On the influence of the CO2 solubility in water on the performance of enhanced oil recovery - Afanasyev, Andrey Aleksandrovich; Andreeva, Anna Igorevna; Sypchenko, Irina Mikhaylovna; Chernova, Anna Aleksandrovna (Computational Continuum Mechanics, 2024)
CO2- enhanced oil recovery (CO2-EOR) methods, which are based on the injection of carbon dioxide (CO2) into the oil reservoir through an oil production well are complicated by  phase transitions and compositional effects. Thus, after penetrating into the oil reservoir, CO2 dissolves not only in oil, but also in water, which always exists in oil-saturated rocks. At temperatures and pressures typical of oil-bearing strata  the concentration of dissolved gas in both these phases can be rather high.  Standard algorithms used to model filtering processes is based on the assumption that the concentration of CO2 in water is zero. Consideration for gas dissolution in water requires the usage of improved algorithms, in which the state of stratum mixtures is calculated using the equations of state rather than correlations derived from the experimental data.. In this paper, we present such an algorithm, which is implemented in our MUFITS reservoir simulator. We then apply it to estimate the influence of the CO2 solubility in water on the oil recovery using carbonized water and supercritical CO2. It has been found that neglecting CO2 solubility results in the underestimation of the oil recovery. We present the qualitative and quantitative estimates of the above phase transition effects on the oil recovery factor. The  simulation demonstrates that the solubility of CO2 in water causes an increase in the oil recovery factor both in the case of injection of carbonated water and supercritical CO2. However, the dissolution of CO2 in water exhibits a rather limited influence on  the multistage mixing during CO2-EOR and as well as on the oil recovery factor. If the solubility of CO2 in water is neglected during simulation, the recovery factor at a later stage of the injection is underestimated only by a few percent.
Keywords: flow in a porous medium; phase transitions; CO2 flooding; oil reservoir; CO2-EOR; numerical modeling